Implementation of the International Association of Diabetes and Pregnancy Study Groups Criteria: Not Always a Cause for Concern - Pooja Sibartie; Julie Quinlivan (Journal of Pregnancy)
Background. Controversy surrounds the decision to adopt the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria for the diagnosis of gestational diabetes mellitus (GDM) as fears that disease prevalence rates will soar have been raised. Aims. To investigate the prevalence of pregnancy complicated with GDM before and after the introduction of the IADPSG 2010 diagnostic criteria. Materials and Methods. A prospective audit of all women who delivered from July 1, 2010, to June 30, 2014, in a predefined geographic region within the North Metropolitan Health Service of Western Australia. Women were diagnosed with GDM according to Australian Diabetes in Pregnancy Society (ADIPS 1991) criteria until December 31, 2011, and by the IADPSG 2010 criteria after this date. Incidence of GDM and predefined pregnancy outcomes were audited. Results. Of 10,296 women, antenatal oral glucose tolerance test (OGTT) results and follow-up data were obtained for 10,103 women (98%), of whom 349 (3.5%) were diagnosed with GDM. The rate of GDM utilising ADIPS criteria was 3.4% and the rate of utilising IADPSG criteria was 3.5% (p=0.92). Conclusion. IADPSG diagnostic criteria did not significantly increase the incidence of GDM in this low prevalence region.